Robot motion planning - Latombe Jean-Claude (Boston Kluwer Academic, 1991)
It discusses a central problem in the development of autonomous robots. Motion planning, the central theme of the book can defined as follows: How can a robot decide what motions to perform in order to achieve goal arrangements of physical objects. It is
Keywords: Robots-motion